Zagadnienia jawności prawa: [Public nature of law] (Studia Prawnicze / The Legal Studies, 1981)
Public nature of law is one of fundamental issues in acting in favour of development of socialist democracy in our country. Although Polish literature is unanimous as to the fact that total openness of law should be guaranteed, in particular problems there are differences of opinions as to e.g. the very way to understand the real contents of notions such as “publication”.Socialist doctrine considers public nature of functioning of state organs one of the fundamental principles of functioning of a socialist state. Every exception to this rule is considered the defection from the very concept of a socialist state. Obviously, the postulate of openness includes also the sphere of law-making. This means, however, not only making known the contents of newly adopted rules to those in whose individuals rights or interests such rules intervene. The doc- trine replaced individual interest by social interest: if a state is to be consi- dered the state of all the working people and if it is to be transformed gra- dually into all-national state, then it is the priviledge of every citizen and the priviledge of all to have full access to a 11 current legal rules gua- ranteed. Thus, justification of the right to know the law in now not only individual interest but first of all participation in governing the state, i.e social motive, the need of social control of the law-making activity of the state.The Author makes a critical presentation of the situation concerning the duty to publish newly adopted legal provisions and of the practice of state organs in this domain which in some respects seems not to be fully conformable to binding laws. The article presents also some propositions de lege ferenda. According to the Author’s opinion the principle of public nature of law should be established in the constitution with an additional condition that only laws may introduce certain categories of legal acts which may remain unpublished in certain specific situations. To this right of every citizen — established by laws - to know the law, specificly defined duties of state organs should correspond. These are first of all popularization and explanation of the contents of binding legal rules.